Effect of process parameters on ice crystals and air bubbles size distributions of sorbets in a scraped surface heat exchanger. (August 2018) - Parra, Oscar Darío Hernández; Ndoye, Fatou-Toutie; Benkhelifa, Hayat; Flick, Denis; Alvarez, Graciela
Highlights: A low-temperature microscopy method was developed for crystals and bubbles size measurement. The influences of refrigerant fluid temperature and air flowrate were investigated. Lowering refrigerant fluid temperature decreased ice crystals and air bubbles sizes. Increasing air flowrate reduces ice crystals size. Changes in air flowrate have a slight impact on air bubbles size. Abstract: Ice crystals and bubbles size distributions were characterized for aerated sorbets produced during a crystallization-foaming process in a scraped surface heat exchanger. Size measurements were performed immediately at the exit of the heat exchanger by means of a low-temperature microscopy method especially developed in order to discriminate between ice crystals and bubbles and to make possible to measure both sizes simultaneously. The influence of process parameters such as refrigerant fluid evaporating temperature and air flowrate on both size distributions was investigated. Larger ice crystals were obtained when refrigerant fluid temperature increased, but this effect was minimized by the presence of air which retards crystal growth by insulation and hindrance effect. Low refrigerant fluid temperature led to small air bubbles size because of the enhancement of bubbles breakup by shear forces. Ice crystals size was reduced when air flowrate was increased, even if the effect was less pronounced at the lower refrigerant fluid temperature. Variations on air flowrate had a very small effect on air bubbles size.